Ekstrak Daun Kenikir (Cosmos caudatus) sebagai Repelen Nyamuk Culex quinquefasciatus - Marlik Marlik; Mareta Ega Pramestari; Ngadino Ngadino (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2022)
Preventing mosquito bites can using repellents. Chemical-based repellents can have an impact on aquatic organisms and skin irritation. Alternative to making repellents that can replace chemicals in order to reduce the negative impacts can using plants, one of which is kenikir leaves in the form of extracts. Purpose of the study was to determine the potential of kenikir leaf extract (Cosmos caudatus) as a mosquito repellent for Culex quinquefasciatus. This research used post test only control group design. Object of the study was female Culex quinquefasciatus mosquitoes aged 2-5 days with 6 repetitions. Ingredients used kenikir leaf extract with concentration of 7%, 9%, and 11%. Analysis using one way Anova. The concentration of kenikir leaf extract 7%, 9%, and 11% can protect the Culex quinquefasciatus mosquito perch with repulsion of 62.7% for 6 minutes, 78% for 10 minutes and 92.7% for 15 minutes. Results showed that was a difference in the average length of time of repulsion at the concentration of kenikir leaf extract 7%, 9%, and 11% against the Culex quinquefasciatus mosquito (p=0.00; p<0.05). Further research is expected to increase concentration of kenikir leaves and addition of other ingredients to increase the length of protection.